Optimal management of elderly patients with glioblastoma - Laperriere, Normand; Weller, Michael; Stupp, Roger; Perry, James R.; Brandes, Alba A.; Wick, Wolfgang; Bent, Martin J. van den (Cancer treatment reviews, 2013)
Median age at diagnosis in patients with glioblastoma (GB) is slowly increasing with an aging population in Western countries, and was 64years in 2006. The number of patients age 65 and older with GB will double in 2030 compared with 2000. Survival in this older cohort of patients is significantly less than seen in younger patients. This may in part be related to more aggressive biology of tumor, reduced use of standard management approaches, increased toxicity of available therapies, and increased presence of comorbidities in this older patient population. Limited data do support the use of more extensive resection in these patients. Randomized data support the use of post-operative radiotherapy (RT) versus supportive care, but do not demonstrate a benefit for the use of the standard 6weeks course of RT over hypofractionated RT given over 3weeks. Preliminary data of randomized studies raise the possibility of temozolomide alone as an option for these patients. The use of 6weeks of RT with concurrent and adjuvant temozolomide has been associated with reasonably good survival in several uncontrolled small series of selected older patients; however, this better outcome may be related to the selection of better prognosis patients rather than the specific therapy utilized. The current National Cancer Institute of Canada (NCIC) and European Organization for Research and Treatment of Cancer (EORTC) CE.6/26062/22061 randomized study of short course RT with or without concurrent and adjuvant temozolomide will help determine the optimal therapy for this older cohort with currently available therapies.
Available online 19 June 2012
Gesehen am 11.10.2021